2020
DOI: 10.1101/2020.04.24.20077735
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel Protein Drug, Novaferon, as the Potential Antiviral Drug for COVID-19

Abstract: BackgroundNovaferon, a novel protein drug approved for the treatment of chronic hepatitis B in China, exhibits potent antiviral activities. We aimed to determine the anti-SARS-CoV-2 effects of Novaferon in vitro, and conducted a randomized, open-label, parallel group study to explore the antiviral effects of Novaferon for COVID-19. Methods In laboratory, the inhibition of Novaferon on viral replication in cells infected withSARS-CoV-2, and on SARS-CoV-2 entry into healthy cells was determined. Antiviral effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…After screening 7285 titles and abstracts and 122 full texts, 32 unique randomised controlled trials were identified that evaluated drug treatments as of 20 July 2020 (fig 1). 30313233343536373839404142434445464748495051 Searches of living evidence retrieval services identified one additional eligible randomised controlled trial 52. Eighteen randomised controlled trials have been published in peer reviewed journals, and 14 only as preprints.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After screening 7285 titles and abstracts and 122 full texts, 32 unique randomised controlled trials were identified that evaluated drug treatments as of 20 July 2020 (fig 1). 30313233343536373839404142434445464748495051 Searches of living evidence retrieval services identified one additional eligible randomised controlled trial 52. Eighteen randomised controlled trials have been published in peer reviewed journals, and 14 only as preprints.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 32 included drug trials, six evaluated treatment against active comparators, 18 evaluated treatment against standard care or placebo, and two evaluated different durations or doses of the same treatment. Our analyses were performed on 26 June 2020 and include 20 randomised controlled trials 3134353637383941424344454647484950Table 1. presents the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two trials compared convalescent plasma added to standard care versus standard care alone [ 40 , 52 ]. The remaining trials and comparisons included hydroxychloroquine with and without azithromycin added to standard care versus standard care alone [ 55 ], hydroxychloroquine versus placebo [ 54 , 68 ], hydroxychloroquine and chloroquine added to standard care versus standard care alone [ 49 ], methylprednisolone added to standard care versus standard care alone [ 57 ], lopinavir–ritonavir versus umifenovir and versus standard care [ 41 ], favipravir versus umifenovir [ 34 ], high-flow nasal oxygenation versus standard mask oxygenation prior to fibreotic tracheal intubation [ 45 ], α-lipoic acid versus placebo [ 47 ], the combination of novaferon plus lopinavir–ritonavir versus novaferon and versus lopinavir–ritonavir [ 46 ], baloxavir marboxil versus favipiravir and versus standard care [ 42 ], 5 versus 10 days of remdesivir [ 38 ], interferon β-1a added to standard care versus standard care alone [ 37 ], colchicine added to standard care versus standard care alone [ 50 ], high-dosage with low-dosage chloroquine diphosphate [ 51 ], intravenous immunoglobulin added to standard care versus standard care alone [ 58 ], ribavirin plus interferon alpha versus lopinavir/ritonavir plus interferon alpha versis ribavirin plus lopinavir/ritonavir plus interferon alpha [ 62 ], darunavir/cobicistat plus interferon alpha-2b versus interferon alpha-2b alone [ 61 ], lincomycin HCl versus azitromycin [ 63 ], 99mTc-methyl diphosphonate (99mTc-MDP) injection added to standard care versus standard care alone [ 64 ], and interferon alpha-2b plus gamma versus interferon alpha-2b alone [ 65 ].…”
Section: Resultsmentioning
confidence: 99%